2011
DOI: 10.1111/j.1651-2227.2011.02258.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma B‐type natriuretic peptide levels in children with heart disease

Abstract: Plasma BNP levels are elevated in children with heart disease before treatment and are a useful laboratory parameter under treatment during long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
(27 reference statements)
1
14
0
1
Order By: Relevance
“…Plasma BNP levels are elevated in adults and children with heart disease and PAH (idiopathic or congenital), so these levels serve as a useful laboratory parameter in medical or surgical treatment [23,24]. In our study we showed that all of the PAH patients had elevated levels of plasma BNP.…”
Section: Discussionsupporting
confidence: 58%
“…Plasma BNP levels are elevated in adults and children with heart disease and PAH (idiopathic or congenital), so these levels serve as a useful laboratory parameter in medical or surgical treatment [23,24]. In our study we showed that all of the PAH patients had elevated levels of plasma BNP.…”
Section: Discussionsupporting
confidence: 58%
“…It plays an important role in the diagnosis and prognosis assessment of this disease, and it is regarded as a specific serum marker and gold standard for CHF diagnosis in recently years. [5][6][7] Carvedilol is a third-generation b-blocker, and clinical trials demonstrated that it can significantly improve the clinical symptoms, prognosis, and survival of patients with CHF. 8,9 This study aimed to observe the changes of serum h-FABP, BNP, and cardiac function before and after treatment with carvedilol in children with CHF and to explore the clinical application of h-FABP, BNP, and the therapeutic effect of carvedilol in children with chronic cardiac insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with structural CHD the range of NP levels varies widely depending on a number of factors including age at time of surgery, type of lesion, stage and type of palliation and duration of CPB (11)(12)(13)26).…”
Section: Discussionmentioning
confidence: 99%